The Jurassic and Deep Structures Inferred from Gravity Data Depending on Stripping Technique for The Uppermost Layers in Central and Southern Iraq - AL-Banna, Ahmed S.; AL-Saffar, Reham S. (Iraqi Journal of Science, 2022)
The gravity anomalies of the Jurassic and deep structures were obtained by stripping the gravity effect of Cretaceous and Tertiary formations from the available Bouguer gravity map in central and south Iraq. The gravity effect of the stripped layers was determined depending on the density log or the density density obtained from the sonic log. The density relation with the seismic velocity of Gardner et al (1974) was used to obtain density from sonic logs in case of a lack of density log. The average density of the Cretaceous and Tertiary formation were determined then the density contrast of these formations was obtained. The density contrast and thickness of all stratigraphic formations in the area between the sea level to the top of Jurassic formations were used to determine the gravity effect of these layers. The gravity anomaly map of the stripped formation was determined. The gravity anomaly map of the stripped formation was subtracted from the Bouguer gravity map, and the gravity anomaly map of deep structures was obtained. The regional and residual maps (3rd order polynomial ) were determined  for the gravity anomaly maps before and after stripping. The regional gravity map before stripping shows one positive anomaly located at the western part of the study area and west Abu-Jir and Euphrates faults. The regional gravity map after stripping shows a positive anomaly located along an axis extended from Kut toward Najaf. This positive anomaly map divided the sedimentary basin into two sub-basins. The positive gravity residual anomaly of the Bouguer map before stripping shows regionally three structural axes trending NW-SE. These axes are Baghdad-Kut axis, northwest Karbala axis and west Samawa- Nasiriyah axis. The positive residual anomaly map after stripping shows two important  anomaly areas. The first area is located between Kut and Karbala-Najaf . and the second is located northwest Karbala by about 100-120 km. These two areas may be prospective areas for hydrocarbon. The stripping method application in the study area shows good result; therefor, it can be used to enhance the gravity data to investigate deep structures in other areas.